(untitled) (Research, Society and Development, 2025)
Autophagy can be defined as a cellular mechanism activated when an organelle is aged or dysfunctional, leading to the degradation of its components for energy production. It acts as a tumor suppressor or oncogenic mechanism, assuming a dubious role in tumorigenesis. Numerous studies have described alterations in the expression of microRNAs (miRNAs) that modulate the autophagic process in different tumor types. This study aimed to review basic concepts about autophagy and identify the main miRNAs that regulate the expression of autophagy-related genes and their role as potential tumor biomarkers. For this purpose, a bibliographic search was carried out in PubMed and Scielo using generic terms. The miRTarBase and DIANA-TarBase v8 public databases were used to collect validated miRNA-target gene interactions, while UALCAN allowed comparing the gene expression profiles of selected miRNAs in normal vs. tumors. The autophagy-related genes with the highest number of miRNAs validated as regulators of their expression were ATG1, ATG9A, ATG16L1, and SQSTM1. We also found three miRNAs (hsa-miR-16-5p, hsa-miR-20a-5p, and hsa-miR-155-5p) that regulate a greater number of autophagy-related genes. Interestingly, hsa-miR-20a-5p showed significant overexpression in prostate, breast, lung, colorectal, and liver tumors. Taken together, these data suggest hsa-miR-20a-5p as the most outstanding miRNA in the regulation of autophagy and a promising biomarker of solid tumors, which requires further studies to validate its role in tumorigenesis.